Anti-erosion protection for recreational and sports facilities - Shcherbina Elena; Afonina Marina (MATEC Web of Conferences, 2016)
Development of natural lands for recreational purposes generates an increasing human impact. The monitoring results show development of slope erosion processes on the surface of slopes, which can generate gullies and landslides, impeding a sustainable land development and requiring additional operational costs at recreational and sports facilities. The article contains the basic results of a theoretical and experimental research and the monitoring data, which will allow us to justify the design of anti-erosion protection at recreational and sports facilities. The research has shown the efficiency of the use of geocomposite systems represented by a combination of structural elements and a biotic constituent. The efficiency of such approach is proven by the geotechnical monitoring data on specific facilities situated in Moscow Region.